A method of high-level disinfection of the root canal system in the treatment of destructive forms of periodontitis (Эндодонтия Today)
In the treatment of patients with destructive forms of periodontitis, the primary role for antimicrobial treatment of the root canal system. In an experiment on extracted teeth, it was tested method of filling the root canal with the help of apparatus EndoActivator® «Dentsply» with a paste of calcium hydroxide in comparison with the traditional method - endodontic files and reamers. A significant improvement in filling the root canal using EndoActivator® «Dentsply» apparatus.